(untitled) (Economics and region, 2025)
The article considers the use of production sharing agreements as a high-yield tool for generating high profitability for the budget of the state-owner of minerals at the level of 60-70% of the total profit from the mining project. In addition, the toolkit allows for the formation of additional related infrastructure, which has a positive impact on the current socio-economic situation. US President Donald Trump announced that he wants to conclude an agreement with Ukraine on providing assistance in exchange for guarantees of access to rare earth metals. Today, there are active discussions regarding the US demand for the transfer of Ukrainian subsoil for use in the amount of 300 billion US dollars. The authors believe that the US proposal is a unique opportunity for Ukraine to effectively develop subsoil, create new jobs, replenish the state budget and develop related businesses that create added value to raw materials. The publication examines the application of an economic and legal instrument - a production sharing agreement - using the experience of Kazakhstan and Ukraine as an example, and also analyzes the localization of rare earth mineral deposits in the country. The analyzed actions of the production sharing agreement demonstrate high profitability from the use of this regulatory instrument for the budget of the state-owner of minerals at the level of 60-70% of the total profit from the mining project. In addition, the toolkit allows for the formation of additional accompanying infrastructure, which has a positive impact on the current socio-economic situation. The Ukrainian model has two significant drawbacks: the relative static resistance of the R-factor and a significant increase in the cost of fouling new wells. That is why the value of the R-factor will be located for a long time in a time interval with a size not exceeding 2, therefore, the participants in the production sharing agreement will be expected to return the investor’s investment for more than a dozen years. Deposits of rare earth minerals in Ukraine are significant, most of them are located in temporarily occupied territories within the Donetsk-Dnieper Basin and the Azov Lowland. Geographically, almost half of the natural resource deposits are occupied. Only within the framework of an absolutely fantastic project of processing the Ukrainian Shield can it be possible to get several hundred billion dollars for its constituent minerals. But the cost of such "utilization" of the Crystal Shield will be comparable to the revenue, if not exceed it once again. What is readily available in Ukraine is iron and manganese ore.